Clostridioides difficile contamination in a clinical microbiology laboratory?. (March 2020) - Reigadas, E.; Vázquez-Cuesta, S.; Onori, R.; Villar-Gómara, L.; Alcalá, L.; Marín, M.; Martin, A.; Muñoz, P.; Bouza, E.
Abstract: Objectives: Clostridioides difficile infection has traditionally been considered to be transmitted predominantly within health-care settings. It is not recognized as a pathogen that presents a risk of laboratory acquisition. Data on laboratory contamination and acquisition by laboratory personnel are lacking. Our objective was to assess environmental contamination by C. difficile and its potential for transmission in a clinical microbiology laboratory. Methods: Laboratory surfaces were screened for C. difficile . Samples were taken in areas that handle C. difficile isolates (high-exposure (HE) areas), areas adjacent to HE areas or those processing faecal samples (medium-exposure (ME) areas), and areas that do not process faecal samples or C. difficile isolates (low-exposure (LE) areas). We examined C. difficile carriage (hands/rectal samples) of laboratory workers. Results: A total of 140 environmental samples were collected from two HE areas ( n  = 56), two ME areas ( n  = 56) and two LE areas ( n  = 28). Overall, 37.8% (37/98) of surfaces were contaminated with C. difficile, and 17.3% (17/98) with toxigenic C. difficile (TCD). HE areas were significantly more contaminated with TCD than LE areas (38.1% (16/42) versus 0.0% (0/14), p 0.005) and ME areas (38.1% (16/42) versus 2.4% (1/42), p <0.001). Hands were colonized with TCD in 11.8% (4/34) of cases. We found no rectal carriage of C. difficile . Conclusions: We found a significant proportion of laboratory surfaces to be contaminated with toxigenic C. difficile, as well as hand colonization of laboratory personnel. We recommend specific control measures for high-risk areas and laboratory personnel working in these areas.